Large-current-density long-term stable electro-catalytic oxygen evolution catalyst as well as preparation method and application thereof

Through the preparation of chromium-doped ruthenium dioxide nanocatalysts, the electron transport capability and Ru-O covalent of the catalyst are regulated, and the problem of insufficient stability of RuO2-based catalysts in acidic OER environment is solved, and long-term stability of large current density is achieved and high catalytic activity, suitable for practical application of PEMWEs technology.

CN119194487APending Publication Date: 2024-12-27NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411470294.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing RuO2-based catalysts are insufficient in acidic OER environments and cannot meet the practical application requirements of PEMWEs technology. In addition, previous adjustment methods focus on unilateral adjustment of synthesis methods or doping, resulting in short catalyst stabilization time and insufficient activity.

Method used

By mixing the salt template, ruthenium salt powder and chromium salt powder for grinding, molten salt reaction and cooling with water, and then etching in an acid solution, chromium-doped ruthenium dioxide nanocatalyst was prepared to regulate the electron transport of the catalyst. The ability and Ru-O are covalent, hinder the dissolution of ruthenium and improve stability.

Benefits of technology

The long-term stability of high current density is achieved. The catalyst can operate stably for 1400 hours at a current density of 10 mA cm-2, and can achieve 1500 mA cm-2 current density in the proton exchange membrane water electrolytic cell and operate continuously for more than 2300 hours. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194487A_ABST
    Figure CN119194487A_ABST
Patent Text Reader

Abstract

The invention discloses a high-current-density long-term stable electrocatalytic oxygen evolution catalyst as well as a preparation method and application thereof, and particularly relates to the field of catalysts. Comprising the following steps: mixing a salt template, ruthenium salt powder and chromium salt powder to obtain mixed powder, and grinding the mixed powder to obtain a precursor; placing the precursor in a reaction container for a molten salt reaction, and cooling a reaction product with water to obtain a catalyst precursor; and adding the catalyst precursor into an acid solution for etching to obtain the high-current-density long-term stable electro-catalytic oxygen evolution catalyst. The electron transmission capability and Ru-O covalence of the catalyst are continuously regulated and controlled at the same time through continuous doping of chromium, the doping amounts of chromium in the catalyst located at the poles of the two are the same, the catalyst has high catalytic activity due to the optimal electron transmission capability and Ru-O covalence, dissolution of ruthenium dioxide in the electrooxidation reaction process is effectively hindered, and the catalytic activity of the catalyst is improved. The stability of the catalyst in an acidic oxygen evolution reaction is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of catalysts, and in particular to a high current density, long-term stable electrocatalytic oxygen evolution catalyst, and a preparation method and application thereof. Background Art

[0002] Proton exchange membrane water electrolyzer (PEMWEs) technology has attracted much attention in the field of electrocatalytic water splitting hydrogen production due to its unique advantages such as no pollution, low ohmic resistance, high hydrogen purity, high working current density and fast response time. Compared with the cathode hydrogen evolution reaction (HER), the anodic oxygen evolution reaction (OER) kinetics involve a slow four-electron transfer process, so it requires a very high overpotential to proceed smoothly, which puts very strict requirements on the stability of the catalyst at high overpotential. At present, iridium (Ir)-based catalysts are the most suitable catalysts for OER in acidic media and high operating voltages, but their relatively low OER activity, high cost and low reserves have become important factors limiting their widespread application. Ruthenium (Ru) is considered to be a promising alternative to iridium. Its oxide (RuO2) shows good OER activity under acidic conditions and is about 8 times cheaper than iridium. However, the oxidation state of Ru in RuO2-based catalysts is easily over-oxidized to high-valent soluble RuO4 species at the OER potential, resulting in Ru desolvation, which leads to a rapid decrease in the activity and stability of the catalyst. Therefore, how to maintain or improve the activity of RuO2-based catalysts while significantly improving the stability of the catalyst is the key to promoting the practical application of PEMWEs technology based on RuO2-based catalysts.

[0003] In order to solve the problem that the stability of RuO2-based catalysts in acidic OER environments is not enough to meet the requirements of replacing IrO2-based catalysts, researchers have preliminarily achieved a win-win situation in the activity and stability of RuO2-based catalysts in the acidic OER process through defect engineering, strain design, doping and other methods. However, the stability of most RuO2-based catalysts developed and verified by these methods can only work stably for tens to hundreds of hours in a small current density range, which is far from meeting the application requirements of PEMWEs under actual working conditions. Adjusting the electron transfer ability and Ru-O covalency of RuO2-based catalysts is considered to be one of the effective strategies to optimize RuO2-based catalysts to obtain excellent acidic OER catalytic activity and stability. However, most previous studies have focused on adjusting the electron transfer ability and Ru-O covalency by monotonically adjusting the synthesis method or screening different metal elements to dope RuO2, which is both one-sided and discontinuous, and the resulting RuO2-based catalysts have a short stability time and insufficient activity. Summary of the invention

[0004] The main purpose of the present application is to provide a high current density, long-term stable electrocatalytic oxygen evolution catalyst and its preparation method and application, aiming to solve the problems of short stability time and insufficient activity of existing commercial catalysts.

[0005] To achieve the above-mentioned purpose, the present application provides a method for preparing a high current density, long-term stable electrocatalytic oxygen evolution catalyst, comprising: mixing a salt template, a ruthenium salt powder and a chromium salt powder to obtain a mixed powder, and grinding the mixed powder to obtain a precursor; placing the precursor in a reaction vessel for a molten salt reaction, and cooling the reaction product with water to obtain a catalyst precursor; wherein, during the molten salt reaction, the temperature is raised to 300-450°C at 5-10°C / min, and the reaction is carried out for 1.5-3 h; the catalyst precursor is added to an acid solution for etching to obtain a high current density, long-term stable electrocatalytic oxygen evolution catalyst.

[0006] Optionally, the salt template is a combination of any two of lithium chloride, sodium chloride, potassium chloride and cesium chloride.

[0007] Optionally, the mass ratio of the two salts in the salt template is 3:2.

[0008] Optionally, the mass ratio of the ruthenium salt powder to the chromium salt powder is 1:0.17-2.7, and the mass ratio of the salt template to the sum of the masses of the ruthenium salt powder and the chromium salt powder is 2:1.

[0009] Optionally, the ruthenium salt is ruthenium acetylacetonate, and the chromium salt is chromium acetylacetonate.

[0010] Optionally, the acid solution is a hydrochloric acid solution.

[0011] Optionally, during the etching process, the etching temperature is 30-60° C. and the etching time is 18-24 h.

[0012] To achieve the above objectives, the present application also provides a high current density, long-term stable electrocatalytic oxygen evolution catalyst, which is prepared by the above-mentioned high current density, long-term stable electrocatalytic oxygen evolution catalyst preparation method.

[0013] Optionally, the chemical formula of the high current density long-term stable electrocatalytic oxygen evolution catalyst is Cr x Ru y O2, where x=0.16~0.71, y=0.29~0.84, x+y=1.

[0014] To achieve the above objectives, the present application also provides a use of the above-mentioned high current density, long-term stable electrocatalytic oxygen evolution catalyst in a proton exchange membrane water electrolyzer.

[0015] Compared with the prior art, the present invention has the following beneficial effects: A method for preparing a catalyst for electrocatalytic oxygen evolution with high current density and long-term stability, wherein the catalyst's electron transport capacity and Ru-O covalency are continuously regulated by continuous chromium doping, and the catalysts at the extremes of the two have the same chromium doping amount. The optimal electron transport capacity and Ru-O covalency make the catalyst have high catalytic activity, and effectively hinder the dissolution of ruthenium dioxide during the electrooxidation reaction, greatly improving the stability of the catalyst in the acidic oxygen evolution reaction; using water as a fast cooling medium, a catalyst with a high curvature surface can be obtained, which is conducive to the diffusion of reactants and bubbles, and enhances the contact between reactants and electrodes and charge transfer; the current can reach 10 mA cm -2 The overpotential of the current density is only 176 mV, and the current density can be 10 mA cm -2 The catalyst was applied to a proton exchange membrane water electrolyzer and could achieve a current density of 1500 mA cm at a low voltage of 1.63 V. -2 The current density was 300 mA cm -2 The high current density can run stably and continuously for more than 2300 hours. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a transmission electron microscope TEM image of the high current density long-term stable electrocatalytic oxygen evolution catalyst prepared in Example 1 of the present application; Figure 2 This is a spherical aberration-corrected high-angle annular dark-field electron microscopy image of the high current density, long-term stable electrocatalytic oxygen evolution catalyst prepared in Example 1 of the present application; Figure 3 Polarization curves of the electrolytic water oxygen evolution reaction of the high current density long-term stable electrocatalytic oxygen evolution catalyst prepared in Examples 1 and 7 of the present application and commercial ruthenium dioxide; Figure 4 The potential variation curve over time of the high current density long-term stable electrocatalytic oxygen evolution catalyst prepared in Examples 1 and 7 of the present application and the commercial ruthenium dioxide electrolysis water oxygen evolution reaction (constant current); Figure 5 This is a transmission electron microscope TEM image of the high current density, long-term stable electrocatalytic oxygen evolution catalyst prepared in Example 2 of the present application; Figure 6 X-ray diffraction XRD diagram of the high current density long-term stable electrocatalytic oxygen evolution catalyst prepared in Examples 1-7 of the present application; Figure 7 Polarization curves of the high current density, long-term stable electrocatalytic oxygen evolution catalyst and commercial ruthenium dioxide prepared in Example 1 of the present application, tested at 80°C in a proton exchange membrane water electrolysis hydrogen production device; Figure 8The high current density long-term stable electrocatalytic oxygen evolution catalyst prepared in Example 1 of the present application is applied to the proton exchange membrane water electrolysis hydrogen production device at 300 mA / cm 2 Stability curve under high current density; The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in this application will be clearly and completely described below in conjunction with the drawings in this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0018] The first embodiment of the present invention provides a method for preparing a high current density long-term stable electrocatalytic oxygen evolution catalyst, which specifically comprises the following steps: Step S1, mixing a salt template, a ruthenium salt powder and a chromium salt powder to obtain a mixed powder, and grinding the mixed powder to obtain a precursor; The salt template is a combination of any two salts of lithium chloride, sodium chloride, potassium chloride and cesium chloride, the mass ratio of the two salts in the salt template is 3:2, the salt template has high ion activity and can promote the diffusion and reaction of the reactants. The mass ratio of ruthenium salt powder to chromium salt powder is 1:0.17-2.7, and the mass ratio of the salt template to the sum of the mass of the ruthenium salt powder and the chromium salt powder is 2:1. The ruthenium salt is ruthenium acetylacetonate, the chromium salt is chromium acetylacetonate, and ruthenium acetylacetonate and chromium acetylacetonate are the sources of metal Ru and Cr. Grinding can be performed in a mortar.

[0019] Step S2, placing the precursor in a reaction vessel for a molten salt reaction, immediately cooling the reaction product with water after the reaction is completed, and obtaining a catalyst precursor after drying; wherein, during the molten salt reaction, the temperature is increased to 300-450°C at 5-10°C / min, and the reaction is carried out for 1.5-3h; Among them, the reaction container can be a muffle furnace. During the molten salt reaction, ruthenium acetylacetonate and chromium acetylacetonate react with oxygen to obtain a chromium-doped ruthenium dioxide electrocatalyst. In this process, since the atomic radius of Cr and Ru is not much different, Cr can continuously enter the RuO2 lattice to replace the position of Ru, and thereby continuously adjust the catalyst's electron transport capacity and Ru-O covalency, effectively hindering the dissolution of ruthenium dioxide during the electro-oxidation reaction; the continuous adjustment of electron transport capacity and Ru-O covalency not only makes the catalyst at the extreme point of the two have high catalytic activity, but also greatly improves its stability in the acidic oxygen evolution reaction. In addition, the reaction product is immediately cooled with water after the reaction is completed. Using water as a rapid cooling medium can obtain a catalyst with a high curvature surface, which is conducive to the diffusion of reactants and bubbles, and enhances the contact between reactants and electrodes and charge transfer.

[0020] Step S3, adding the catalyst precursor to an acid solution for etching, centrifuging, washing, separating and drying the etched product to obtain a ruthenium dioxide nanocatalyst continuously doped with chromium, i.e., a high current density, long-term stable electrocatalytic oxygen evolution catalyst, whose chemical formula is Cr x Ru y O2, where x is 0.16~0.71, y is 0.29~0.84, and the sum of x and y is 1.

[0021] The acid solution is a hydrochloric acid solution with a molar concentration of 0.1 M. During the etching process, the etching temperature is 30-60° C. and the etching time is 18-24 hours. The salt template can be removed by etching.

[0022] Example 1 Preparation of chromium-doped ruthenium dioxide nanocatalyst Step S1, at room temperature, 120 mg of lithium chloride powder, 80 mg of sodium chloride powder, 70 mg of ruthenium acetylacetonate powder and 30 mg of chromium acetylacetonate powder are mixed to obtain a mixed powder, the mixed powder is added into a mortar, and the mixed powder is continuously ground at room temperature until it is uniform to obtain a precursor; Step S2, placing the precursor in a muffle furnace, heating it to 400° C. at a rate of 10° C. / min, reacting it for 2 hours, and immediately taking it out after the reaction is completed and cooling the reaction product with water, and drying it to obtain a catalyst precursor; Step S3, adding the catalyst precursor to a 0.1M HCl solution, stirring and etching at 60°C for 18 hours; after the etching is completed, the product is centrifuged, washed with water and ethanol, separated, and dried to obtain a ruthenium dioxide nanocatalyst continuously doped with chromium, that is, a high current density, long-term stable electrocatalytic oxygen evolution catalyst.

[0023] The chromium continuously doped ruthenium dioxide nanocatalyst prepared in this example was tested, and its transmission electron microscope TEM image and spherical aberration corrected high-angle annular dark field electron microscope image were as follows: Figure 1 , 2 As shown, from Figure 1 It can be seen that there are sharp protrusions on the catalyst surface, proving that the method of this embodiment can enable the catalyst to obtain a surface with high curvature. Figure 2 It can be seen that the lattice spacing of RuO2 (110) and (101) planes in the figure is smaller than that of the standard, indicating that Cr with a smaller atomic radius is doped into the RuO2 lattice.

[0024] The electrochemical performance of the chromium continuously doped ruthenium dioxide nanocatalyst prepared in this example was tested, and its LSV curve and chronopotentiometry curve were as follows: Figure 3 , 4 As shown, it can be seen that the catalyst reaches 10 mA cm -2 The overpotential of the current density is only 176 mV, and the current density can be 10 mA cm -2 It can run stably for 1400 h at a current density of 1.500 W with almost no attenuation.

[0025] Example 2 Preparation of chromium-doped ruthenium dioxide nanocatalyst Step S1, at room temperature, 120 mg of lithium chloride powder, 80 mg of sodium chloride powder, 27 mg of ruthenium acetylacetonate powder and 73 mg of chromium acetylacetonate powder are mixed to obtain a mixed powder, the mixed powder is added into a mortar, and the mixed powder is continuously ground at room temperature until it is uniform to obtain a precursor; Step S2, placing the precursor in a muffle furnace, heating it to 450° C. at a rate of 10° C. / min, reacting it for 1.5 hours, and immediately taking it out after the reaction is completed, cooling the reaction product with water, and drying it to obtain a catalyst precursor; Step S3, adding the catalyst precursor to a 0.1M HCl solution, stirring and etching at 60°C for 24 hours; after the etching is completed, the product is centrifuged, washed with water and ethanol, separated, and dried to obtain a ruthenium dioxide nanocatalyst continuously doped with chromium, that is, a high current density, long-term stable electrocatalytic oxygen evolution catalyst.

[0026] The chromium continuously doped ruthenium dioxide nanocatalyst prepared in this example was tested, and its transmission electron microscope TEM image is as follows: Figure 5 As shown, it can be seen that there are sharp protrusions on the catalyst surface, proving that this method can enable the catalyst to obtain a surface with a high curvature.

[0027] Example 3 Preparation of chromium-doped ruthenium dioxide nanocatalyst Step S1, at room temperature, 120 mg of lithium chloride powder, 80 mg of sodium chloride powder, 85 mg of ruthenium acetylacetonate powder and 15 mg of chromium acetylacetonate powder are mixed to obtain a mixed powder, the mixed powder is added into a mortar, and the mixed powder is continuously ground at room temperature until it is uniform to obtain a precursor; Step S2, placing the precursor in a muffle furnace, heating it to 300° C. at a rate of 10° C. / min, reacting for 3 hours, and immediately taking it out after the reaction is completed and cooling the reaction product with water, and drying it to obtain a catalyst precursor; Step S3, adding the catalyst precursor to a 0.1M HCl solution, stirring and etching at 30°C for 18 hours; after the etching is completed, the product is centrifuged, washed with water and ethanol, separated, and dried to obtain a ruthenium dioxide nanocatalyst continuously doped with chromium, that is, a high current density, long-term stable electrocatalytic oxygen evolution catalyst.

[0028] Example 4 Preparation of chromium-doped ruthenium dioxide nanocatalyst Step S1, at room temperature, 120 mg of lithium chloride powder, 80 mg of sodium chloride powder, 53 mg of ruthenium acetylacetonate powder and 47 mg of chromium acetylacetonate powder are mixed to obtain a mixed powder, the mixed powder is added into a mortar, and the mixed powder is continuously ground at room temperature until it is uniform to obtain a precursor; Step S2, placing the precursor in a muffle furnace, heating it to 350° C. at 5° C. / min, reacting for 2.5 hours, and immediately taking out the reaction product after the reaction is completed, cooling it with water, and drying it to obtain a catalyst precursor; Step S3, adding the catalyst precursor to a 0.1M HCl solution, stirring and etching at 50°C for 20 hours; after the etching is completed, the product is centrifuged, washed with water and ethanol, separated, and dried to obtain a ruthenium dioxide nanocatalyst continuously doped with chromium, that is, a high current density, long-term stable electrocatalytic oxygen evolution catalyst.

[0029] Example 5 Preparation of chromium-doped ruthenium dioxide nanocatalyst Step S1, at room temperature, 120 mg of lithium chloride powder, 80 mg of sodium chloride powder, 36 mg of ruthenium acetylacetonate powder and 64 mg of chromium acetylacetonate powder are mixed to obtain a mixed powder, the mixed powder is added into a mortar, and the mixed powder is continuously ground at room temperature until it is uniform to obtain a precursor; Step S2, placing the precursor in a muffle furnace, heating it to 450° C. at 5° C. / min, reacting for 2 hours, and immediately taking it out after the reaction is completed and cooling the reaction product with water, and drying it to obtain a catalyst precursor; Step S3, adding the catalyst precursor to a 0.1M HCl solution, stirring and etching at 50°C for 18 hours; after the etching is completed, the product is centrifuged, washed with water and ethanol, separated, and dried to obtain a ruthenium dioxide nanocatalyst continuously doped with chromium, that is, a high current density, long-term stable electrocatalytic oxygen evolution catalyst.

[0030] Example 6 Preparation of chromium-doped ruthenium dioxide nanocatalyst Step S1, at room temperature, 120 mg of lithium chloride powder, 80 mg of sodium chloride powder, 77 mg of ruthenium acetylacetonate powder and 23 mg of chromium acetylacetonate powder are mixed to obtain a mixed powder, the mixed powder is added into a mortar, and the mixed powder is continuously ground at room temperature until it is uniform to obtain a precursor; Step S2, placing the precursor in a muffle furnace, heating it to 300° C. at a rate of 5° C. / min, reacting it for 2 hours, and immediately taking it out after the reaction is completed and cooling the reaction product with water, and drying it to obtain a catalyst precursor; Step S3, adding the catalyst precursor to a 0.1M HCl solution, stirring and etching at 40°C for 22 hours; after the etching is completed, the product is centrifuged, washed with water and ethanol, separated, and dried to obtain a ruthenium dioxide nanocatalyst continuously doped with chromium, that is, a high current density, long-term stable electrocatalytic oxygen evolution catalyst.

[0031] Example 7 Preparation of Ruthenium Dioxide Nanocatalyst Step S1, at room temperature, 120 mg of lithium chloride powder, 80 mg of sodium chloride powder, and 100 mg of ruthenium acetylacetonate powder are mixed to obtain a mixed powder, the mixed powder is added into a mortar, and the mixed powder is continuously ground at room temperature until it is uniform to obtain a precursor; Step S2, placing the precursor in a muffle furnace, heating it to 400° C. at a rate of 5° C. / min, reacting it for 2 hours, and immediately taking it out after the reaction is completed and cooling the reaction product with water, and drying it to obtain a catalyst precursor; Step S3, adding the catalyst precursor to a 0.1M HCl solution, stirring and etching at 40°C for 22 hours; after the etching is completed, the product is centrifuged, washed with water and ethanol, separated, and dried to obtain a ruthenium dioxide nanocatalyst.

[0032] The electrochemical performance of the ruthenium dioxide nanocatalyst prepared in this example was tested, and its LSV curve and chronopotentiometry curve were as follows: Figure 3 , 4 As shown, it can be seen that the catalyst reaches 10 mA cm -2 The overpotential required for the current density of 270 mV is lower than that of commercial ruthenium dioxide (ComRuO2), but much higher than that of the catalyst prepared in Example 1. -2 It is difficult to operate stably at a current density of 1.5 %. This shows that continuous chromium doping can continuously adjust the electron transfer ability of the catalyst and the Ru-O covalency.

[0033] The high current density long-term stable electrocatalytic oxygen evolution catalyst prepared in Example 1-7 was tested by ICP-MS, and its metal content was obtained as shown in Table 1. The catalyst prepared in Example 1-7 was tested, and its X-ray diffraction XRD pattern was as shown in Figure 6 As shown, it is Figure 6 It can be seen that the catalyst Cr of Examples 1-60.16 Ru 0.84 O2 retains the clear characteristic peaks of ruthenium dioxide, proving that the metal chromium doping does not change the structure of ruthenium dioxide, and does not form a complex of ruthenium oxide and chromium oxide. At the same time, as the amount of chromium doping continues to increase, the XRD diffraction peak gradually moves toward the high angle direction, indicating that Cr with a smaller atomic radius can be continuously doped into the RuO2 lattice.

[0034] Table 1 Catalyst metal content obtained in Examples 1-6

[0035] The second embodiment of the present invention provides a high current density long-term stable electrocatalytic oxygen evolution catalyst, which is prepared by the above-mentioned high current density long-term stable electrocatalytic oxygen evolution catalyst preparation method, and its chemical formula is Cr x Ru y O2, where x=0.16~0.71, y=0.29~0.84, x+y=1.

[0036] The third embodiment of the present invention provides an application of a high current density, long-term stable electrocatalytic oxygen evolution catalyst in a proton exchange membrane water electrolyzer.

[0037] The chromium-doped ruthenium dioxide nanocatalyst prepared in Example 1 was applied to a proton exchange membrane water electrolysis hydrogen production device. At 80°C, the ruthenium dioxide nanocatalyst Cr doped with chromium prepared in Example 1 0.31 Ru 0.69 O2 is used as anode, 20% Pt / C catalyst is used as cathode, deionized water is used as electrolyte, and proton exchange membrane N117 is used as proton exchange membrane. The polarization curve of the water electrolysis hydrogen production device is shown in the figure below. Figure 7 As shown, from Figure 7 As can be seen from the figure, the catalyst only needs an electrolyzer voltage of 1.63 V to reach 1.5 A cm -2 Current density. The cell pressure of the water electrolysis hydrogen production device changes with time. Figure 8 As shown, from Figure 8 It can be seen that Cr 0.31 Ru 0.69 O2 can be at 300mA / cm 2 The current density was maintained for more than 2300 h.

[0038] It can be proved that the ruthenium dioxide nanocatalyst continuously doped with chromium of the present invention realizes the continuous regulation of the catalyst Ru-O covalency and electron transfer ability through the continuous doping of metal chromium, and effectively hinders the dissolution of ruthenium dioxide during the electro-oxidation reaction. Therefore, the ruthenium dioxide nanocatalyst continuously doped with chromium has both efficient electrocatalytic activity and good stability in the electrolysis of water to produce oxygen in an acidic electrolyte.

[0039] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A method for preparing a high current density, long-term stable electrocatalytic oxygen evolution catalyst, characterized in that: include: Mixing the salt template, ruthenium salt powder and chromium salt powder to obtain a mixed powder, and grinding the mixed powder to obtain a precursor; The precursor is placed in a reaction vessel for a molten salt reaction, and the reaction product is cooled with water to obtain a catalyst precursor; wherein, during the molten salt reaction, the temperature is increased to 300-450°C at 5-10°C / min and the reaction is carried out for 1.5-3 hours; The catalyst precursor is added into an acid solution for etching to obtain a high current density and long-term stable electrocatalytic oxygen evolution catalyst.

2. The method for preparing a high current density long-term stable electrocatalytic oxygen evolution catalyst according to claim 1, characterized in that: The salt template is a combination of any two of lithium chloride, sodium chloride, potassium chloride and cesium chloride.

3. The method for preparing a high current density long-term stable electrocatalytic oxygen evolution catalyst according to claim 2, characterized in that: The mass ratio of the two compounds in the salt template is 3:

2.

4. The method for preparing a high current density long-term stable electrocatalytic oxygen evolution catalyst according to claim 1, characterized in that: The mass ratio of the ruthenium salt powder to the chromium salt powder is 1:0.17-2.7, and the mass ratio of the salt template to the sum of the masses of the ruthenium salt powder and the chromium salt powder is 2:

1.

5. The method for preparing a high current density long-term stable electrocatalytic oxygen evolution catalyst according to claim 1, characterized in that: The ruthenium salt is ruthenium acetylacetonate, and the chromium salt is chromium acetylacetonate.

6. The method for preparing a high current density long-term stable electrocatalytic oxygen evolution catalyst according to claim 1, characterized in that: The acid solution is a hydrochloric acid solution.

7. The method for preparing a high current density long-term stable electrocatalytic oxygen evolution catalyst according to claim 1, characterized in that: During the etching process, the etching temperature is 30-60° C. and the etching time is 18-24 h.

8. A high current density, long-term stable electrocatalytic oxygen evolution catalyst, characterized in that: The catalyst is prepared by the method for preparing a high current density, long-term stable electrocatalytic oxygen evolution catalyst according to any one of claims 1 to 7.

9. The high current density long-term stable electrocatalytic oxygen evolution catalyst according to claim 8, characterized in that: The chemical formula of the high current density long-term stable electrocatalytic oxygen evolution catalyst is Cr x Ru y O2, wherein x=0.16~0.71, y=0.29~0.84, and x+y=1.

10. Use of the high current density, long-term stable electrocatalytic oxygen evolution catalyst as claimed in claim 8 in a proton exchange membrane water electrolyzer.

Citation Information

Cited By

  • Preparation method and application of Gd-doped rutile ruthenium dioxide nanosheet

    CN119663364A

  • Preparation method of manganese-doped nickel sulfide / porous foamed nickel electrode for bifunctional alkaline electrolytic water

    CN120138693A

  • A preparation method of a bifunctional alkaline electrolytic water manganese-doped nickel sulfide / porous nickel foam electrode

    CN120138693B

  • Tin-doped iridium ruthenium solid solution oxide electrocatalyst as well as preparation method and application thereof

    CN120797059A